Infrared Thermal Imaging Has the Potential to Reduce Unnecessary Surgery and Delays to Necessary Surgery in Burn Patients. Issue 6 (November 2016) - Singer, Adam J.; Relan, Pryanka; Beto, Leonelle; Jones-Koliski, Lisa; Sandoval, Steven; Clark, Richard A.F.
Abstract : Clinical distinction between superficial and deep burns is problematic. The authors determined whether an infrared thermal imaging (IRTI) camera could predict burn depth. Burn depth was assessed by an experienced surgeon, and the burns were imaged with a portable, lightweight IRTI camera that measures heat emission from the skin using long infrared wavelengths (7.5–13 μm). Burns were considered "deep" if they were surgically excised and confirmed to be of full thickness on microscopic evaluation or if they did not heal spontaneously within 21 days of injury. All other burns were considered "nondeep." There were 39 burns that had both days 1 and 2 IRTI measurements and available outcome. Of these, 16 were "deep" burns and 23 were "nondeep." The mean temperatures of "nondeep" burns between days 1 and 2 increased from 30.6 ± 2.7 to 32.1 ± 3.0°C (difference of 1.5 ± 2.3°C). The mean temperatures of "deep" burns decreased from 32.3 ± 2.0 to 30.8 ± 1.3°C (difference of −1.5 ± 2.0°C) between days 1 and 2. Any decrease in temperatures between days 1 and 2 was predictive of a deep wound, and any increase between days 1 and 2 was predictive of a nondeep burn. Using the ultimate burn depth as the criterion standard, the overall accuracy of IRTI was considerably higher than that of clinical assessment; 87.2% (95% CI: 71.8–95.2) vs 54.1% (95% CI: 37.1–70.2). Any decrease in temperatures between days 1 and 2 was predictive of a deep wound. Our results suggest that thermography using IRTI is more accurate than clinical examination in predicting burn depth and could potentially reduce unnecessary surgery as well as reduce delays to surgery when necessary.